2011
DOI: 10.1007/s11274-011-0835-y
|View full text |Cite
|
Sign up to set email alerts
|

An effective and simplified scale-up strategy for acarbose fermentation based on the carbon source control

Abstract: The scale-up strategy for acarbose fermentation by Actinoplanes sp. A56 was explored in this paper. The results obtained in shake-flask cultivation demonstrated that the ratio of maltose and glucose had significant effects on the biosynthesis of acarbose, and the feeding medium containing 3:1 (mass ratio) of maltose and glucose was favorable for acarbose production. Then the correlation of the carbon source concentration with acarbose production was further investigated in 100-l fermenter, and the results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Moreover, the by-product component C was seen to decrease by 90% to 43 mg/l when compared with the levels obtained in the absence of valienamine. Besides our own previous study [21], until the present time, the maximal acarbose titer in fermentation broth was obtained by Li et al [13] at 4,327 mg/l in a 30 L fermentor by a fedbatch process, when controlling total sugar and reducing sugar at 75-80 and 45-50 g/l, respectively. S-Adenosylmethionine (SAM), a ubiquitous substance in living organisms, is generally known to be a methyl donor in various biosynthetic processes.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the by-product component C was seen to decrease by 90% to 43 mg/l when compared with the levels obtained in the absence of valienamine. Besides our own previous study [21], until the present time, the maximal acarbose titer in fermentation broth was obtained by Li et al [13] at 4,327 mg/l in a 30 L fermentor by a fedbatch process, when controlling total sugar and reducing sugar at 75-80 and 45-50 g/l, respectively. S-Adenosylmethionine (SAM), a ubiquitous substance in living organisms, is generally known to be a methyl donor in various biosynthetic processes.…”
supporting
confidence: 51%
“…Complex carbon sources consisting of glucose and maltose are the preferable carbon sources for cell growth and acarbose biosynthesis [4,13,22]. Glucose has always been regarded as the most easily utilizable carbon source.…”
Section: Effects Of Glucose Concentrations On the Process Of Acarbosementioning
confidence: 99%
“…To increase the yield of acarbose, producing strains have been continuously selected by conventional mutagenesis and screening, along with appropriate optimization of fermentation processes, including media, osmolality, and fed-batch culture [4] , [5] , [6] , [7] . In addition, Actinoplanes sp.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable improvements on acarbose titer, acarbose productivity, and proportion of acarbose/impurity C were successfully achieved when 20 mg/L of validamine was added in the fermentation medium prior to inoculation both in batch and fed-batch cultures. The acarbose titer and acarbose productivity obtained in fed-batch culture in this work are the highest that have been reported for all the submerged fermentations of A. utahensis [10, 1215, 19, 20, 27]. This simple and effective strategy would be of great value to acarbose production on commercial scale.…”
Section: Discussionmentioning
confidence: 52%
“…However, major difficulties still exist in improving the yield of acarbose, leading to a high cost for its manufacture. Recently, Li et al [12, 13] reported the medium optimization and scale-up strategy for acarbose fermentation by Actinoplanes sp. A56 and developed an optimized industrial fermentation processes for acarbose production, as a result about 5000 mg/L of acarbose was obtained.…”
Section: Introductionmentioning
confidence: 99%